COMPOSICIÓN QUÍMICA DEL ACEITE ESENCIAL DE Aloysia triphylla “CEDRÓN” COMO INSUMO PARA LA ELABORACIÓN DE UN ENJUAGUE BUCAL - Huerta Leon, Jenny Rosalyn (2020)
Objectives: To determine the chemical composition of the essential oil of Aloysia triphylla “Cedrón”, obtained from the leaves and stems by the steam entrainment method, which in turn serves as an input for the preparation of a mouthwash that can combat halitosis. Materials and methods: The plant material was collected from the city of Huaraz and dried to the environment, the extraction of the essential oil was carried out by the hydrodistillation method with steam drag at controlled temperature and pressure, it was stored in a jar of amber glass in refrigeration. The yield was determined by the volumetric gravimetric method. The determination of the chemical components was carried out by the method of gas chromatography coupled to mass spectrometry using an Agilent Technologies 7890 gas chromatograph, Agilent Technologies 5975C mass spectrometer detector, Column J&W 122-1545.67659 DB-5ms, 325 ° C 60m x 250 μm x 0.25 μm. Results: A yield percentage of 0.13% was obtained. Regarding the chemical composition of the essential oil, 23 compounds identified by retention times were found and 15.62% of Limonene, 18.15% of β-citral and 25.13% of α-citral were obtained as the volatile compounds of higher concentration present in essential oil. Conclusions: It is concluded that, according to the determination of the compounds present in a higher percentage such as Limonene, β-citral and α-citral with antibacterial properties, a mouthwash can be elaborated for the treatment of halitosis produced by the metabolism of bacteria in the oral cavity.